ANALYSIS OF MATHEMATIC REPRESENTATION ABILITY OF JUNIOR HIGH SCHOOL STUDENTS IN THE IMPLEMENTATION OF GUIDED INQUIRY LEARNING - Yumiati Yumiati; Mery Noviyanti (Jurnal Infinity, 2017)
The objective of this research is to analysing the different on upgrade the student’s math representation that obtained the guided inquiry learning and conventional learning. This research conducted by applying experiment method with nonequivalent control group design at one school. Which becoming research subject are students of Dharma Karya UT Middle School at 8th Grade. 8-2 class selected as control class (19 students) and 8-3 class selected as experiment class (20 students). Before and after learning process, two classes given the test of math representation with reliability is 0.70 (high category). The magnitude of the increasing in students’ math representation student group of guided inquiry learning group is 0.41 included as medium category. Meanwhile, the increasing students’ math representation student group of conventional learning is 0.26 included as low category. In conclusion, the hypothesis of the ability of the mathematical representation of students who learning with guided inquiry is better than students with conventional learning is accepted.